Pengetahuan Program Generasi Berenencana (Genre) Di Masa Pandemi Covid-19 Berhubungan Dengan Kesehatan Reproduksi Remaja - Wulandari, Apri Lesi; Lestari, Gangsar Indah (MIDWIFERY JOURNAL, 2022)
Introduction: The planned generation program (GenRe) is a government policy to address population problems in Indonesia. This policy is mandated by the BKKBN. The purpose of the GenRe Program is to facilitate young people to learn to understand and practice healthy and ethical living behaviors to achieve youth resilience as the basis for creating Happy and Prosperous Small Families, to prevent young people from getting married early and knowledge about generation planning is still low at 48.4% in survey 2014. This study aims to determine the relationship between GenRe program knowledge during the Covid-19 pandemic and reproductive health knowledge at SMA N 1 Gedong Tataan. Methods: This research is a quantitative analytic study with a cross-sectional study design. The population is 354 students and the total sample is 188 students. The method of collecting data from this study was by means of a questionnaire, distributed online to students of SMA N 1 Gedong Tataan and then submitted online to a number of subjects to obtain responses and process data by processing and analyzing the data that has been collected. The analysis used was univariate and bivariate (Chi Square test). Results: Research on knowledge of generation planning programs was not good, namely 87 respondents (46.3%), and adolescent reproductive health was not good, namely 68 respondents (36.2%). The results of bivariate analysis showed that there was a good relationship between knowledge of generation planning programs and adolescent reproductive health (53.7%) with a p-value: 0.000 (p-value ≤ 0.05) Conclusion: The results of this study are that there is a relationship between the knowledge of the generation of planning on the reproductive health of adolescents at SMA N 1 Gedong Tataan. Suggestions are that teacher staff and school health workers can work together with researchers to carry out health promotion so that adolescents can know the importance of knowledge of generation planning programs on reproductive health. Suggestion: It is hoped that this research will be useful for the development of midwifery, especially obstetrics for adolescent reproductive health, the application of theories related to knowledge of generation planning programs during the Covid-19 pandemic at SMA N 1 Gedong Tataan can be a source of information regarding the relationship between knowledge of generation planning programs on adolescent reproductive health. Keywords: GenRe Program, Knowledge, Youth Health Care ABSTRAK Pendahuluan : Program generasi berencana (GenRe) merupakan kebijakan dari pemerintah guna mengatasi permasalahan kependudukan di Indonesia. Kebijakan ini diamanahkan oleh BKKBN. Tujuan dari Program GenRe adalah memfasilitasi remaja belajar memahami dan mempraktikkan perilaku hidup sehat dan berahlak untuk mencapai ketahanan remaja sebagai dasar mewujudkan Keluarga Kecil Bahagia dan Sejahtera, guna mencegah remaja dari pernikahan dini dan pengetahuan tentang generasi berencana yang masih rendah yakni sebesar 48,4% pada survey 2014. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan program GenRe di masa pandemi Covid-19 terhadap pengetahuan kesehatan reproduksi di SMA N 1 Gedong Tataan. Metode : Penelitian ini adalah analitik kuantitatif dengan rancangan penelitian cross sectional. Populasi sebanyak 354 siswa dan siswi dan jumlah sampel sebanyak 188 siswa dan siswi. Cara pengumpulan data dari penelitian ini adalah dengan cara angket, dibagikan secara daring kepada siswa/siswi SMA N 1 Gedong tataan kemudian di ajukan secara daring kepada sejumlah subjek untuk mendapatkan tanggapan dan emproses data dengan mengolah dan menganalisis data yang telah terkumpul. Analisis yang digunakan adalah univariat dan bivariat (uji Chi Square). MJ (Midwifery Journal), Vol 2, No. 3. September 2022, ISSN (Cetak) 2775-393X ISSN (Online) 2746-7953, Hal 112-120 113 Hasil : Penelitian pengetahuan program generasi berencana kurang baik yaitu sebanyak 87 responden (46,3%), dan kesehatan reproduksi remaja kurang baik yaitu sebanyak 68 responden (36.2%). Hasil analisis bivariat menunjukan hubungan pengetahua program generasi berencana terhadap kesehatan reproduksi remaja baik yaitu (53,7%) dengan nilai p value : 0,000 (p-value ≤ 0,05) Simpulan : Hasil penelitian ini adalah terdapat hubungan antara pengetahuan generasi berencana terhadap kesehatan reproduksi remajadi SMA N 1 Gedong Tataan. Saran yang diharapkan staf guru dan petugas kesehatan sekolah dapat bekerja sama dengan peneliti untuk melakukan promosi kesehatan agar remaja dapat mengetahui pentingnya pengetahuan program generasi berencana terhadap kesehatan reproduksi. Saran : Diharapan penelitian ini bermanfaat bagi pengembangan ilmu kebidanan khususnya ilmu kebidanan kesehatan reproduksi remaja, penerapan teori-teori yang berkaitan dengan pengetahuan program generasi berencana di masa pandemic covid-19 di SMA N 1 Gedong Tataan dapat menjadi sumber informasi mengenai hubungan pengetahuan program generasi berencana terhadap kesehatan reproduksi remaja. Kata Kunci : Kespro Remaja, Pengetahuan, Program GenRe